Inactivation of the conserved protease LonA increases production of xylanase and amylase in Bacillus subtilis - Biwen Wang; Mariah B. M. J. Kes; Anna C. H. van den Berg van Saparoea; Gaurav Dugar; Joen Luirink; Leendert W. Hamoen (Microbial Cell Factories)
Abstract Background Bacillus subtilis is widely used for industrial enzyme production due to its capacity to efficiently secrete proteins. However, secretion efficiency of enzymes varies widely, and optimizing secretion is crucial to make production commercially viable. Previously, we have shown that overexpression of the xylanase XynA lowers expression of Clp protein chaperones, and that inactivation of CtsR, which regulates and represses clp transcription, increases the production of XynA. In the current study, we examined whether the same is the case for overexpression of the α-amylase AmyM from Geobacillus stearothermophilus by B. subtilis, and why XynA shows a different timing of secretion compared to AmyM. Results Transcriptome analyses revealed that B. subtilis cells overexpressing AmyM exhibited a distinct profile compared to XynA overexpressing cells, however there were also similarities and in both cases expression of CtsR controlled genes was downregulated. In contrast to XynA, inactivation of CtsR did not improve AmyM production. Upregulation of other protein chaperones, including GroEL/ES and DnaJ/K, by inactivating their transcriptional repressor HrcA, had almost no effect on XynA yields and in fact considerably lowered that of AmyM. Despite using the same promoter, the production of XynA peaks well before AmyM reaches its optimal secretion rate. Transcriptome and ribosome profiling indicated that this is neither related to transcription nor to translation regulation. We show that the reduced secretion in the stationary phase is partially due to the activity of secreted proteases, but also due to the activity of the intracellular protease LonA. The absence of this protein resulted in a 140% and 20% increased production for XynA and AmyM, respectively. Conclusion The combination of transcriptome and ribosome profiling offered important information to determine at which cellular level production bottlenecks occurred. This helped us to identify LonA protease as an important factor influencing enzyme production yields in B. subtilis.